2006
DOI: 10.1557/jmr.2006.0019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of representative methods for determining Young's modulus and hardness from instrumented indentation data

Abstract: The effectiveness of Oliver & Pharr's (O&P's) method, Cheng & Cheng's (C&C's) method, and a new method developed by our group for estimating Young's modulus and hardness based on instrumented indentation was evaluated for the case of yield stress to reduced Young's modulus ratio ( y /E r ) у 4.55 × 10 −4 and hardening coefficient (n) р 0.45. Dimensional theorem and finite element simulations were applied to produce reference results for this purpose. Both O&P's and C&C's methods overestimated the Young's modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The physical thicknesses of the coatings were measured from section microstructure. The hardness and modulus of the coatings were measured by nano-indenter (nano-indenter Ò XP) [11]. The chemical composition and valence states of the coatings were studied in detail by XPS (ThermoScientific ESCALAB250, American) with a HSA analyser [12].…”
Section: Methodsmentioning
confidence: 99%
“…The physical thicknesses of the coatings were measured from section microstructure. The hardness and modulus of the coatings were measured by nano-indenter (nano-indenter Ò XP) [11]. The chemical composition and valence states of the coatings were studied in detail by XPS (ThermoScientific ESCALAB250, American) with a HSA analyser [12].…”
Section: Methodsmentioning
confidence: 99%
“…We also propose that nanoindentation [Turner et al, 1999;Van Landingham, 2003;Radovic et al, 2004;Chen et al, 2006;Kim et al, 2006;Ma et al, 2006;Orso et al, 2006] is a promising technique for ascertaining mechanical properties of bone samples too small to test by conventional material testing, and for resolving variation in mechanical properties on a microscopic scale. This approach employs a microscopic indenter, typically 1-10 m in diameter, that can be applied to a prepared surface with a small, precisely measured force, in the range of tens to hundreds of millinewtons, to a controlled depth, typically hundreds to thousands of nanometers.…”
Section: Mechanical Properties Of Bat Wing Bonesmentioning
confidence: 99%
“…In our previous work, 15 it was demonstrated that for W e /W < 0.25, the Oliver & Pharr hardness may be very different from the real hardness (≡ indentation load/real projected contact area). In addition, the relationships established to correlate a true hardness with a representative yield are not applicable to the Oliver & Pharr hardness.…”
Section: Dimensional and Finite Element Analyses Of Hypotheticalmentioning
confidence: 95%